Genetic enhancement for grain yield and mungbean yellow mosaic India virus (MYMIV) resistance through introgressions from Glycine soja: Genetic enhancement for grain yield and mungbean yellow mosaic India virus (MYMIV) resistance through introgressions from Glycine soja - SHIVAKUMAR MARANNA; GIRIRAJ KUMAWAT; VENNAMPALLY NATARAJ; BALWINDER S GILL; RAGHAVENDRA MADAR; SANJAY GUPTA (Journal of Oilseeds Research, 2023)
The current study aimed at development of early maturing, mungbean yellow mosaic India virus (MYMIV) resistant and higher yield soybean genotypes. Through a series of backcrosses (BC4 generation) MYMIV resistance gene has been introgressed from G. soja in to a widely adaptable cultivar JS 335. Introgression lines, viz., YMV1, YMV2, YMV 11 and YMV 16 having MYMIV resistance and higher yield performance over recurrent parent and other check varieties were identified and characterized. GGE biplots analysis revealed YMV 16 as ideal genotype with respect to 100-seed weight and grain yield whereas YMV 11 was promising under sugarcane-soybean intercropping system in spring season. Further, study also reports the development of an extra-early maturing (72 days) genetic stock NRC 252, which can be a potential parent in breeding for early maturing soybean varieties. In conclusion, alleles from wild type soybean could improve yield and MYMIV resistance in cultivated soybean. The genotypes developed in the present study will help in reducing the damage caused by MYMIV disease and area expansion of the soybean crop through intercropping with sugarcane.